K2-290: a warm Jupiter and a mini-Neptune in a triple-star system - Hjorth-Jensen, Morten; Heeren, Paul (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We report the discovery of two transiting planets orbiting K2-290 (EPIC 249624646), a bright (V = 11.11) late F-type star residing in a triple-star s